The meiosis‐specific APC activator FgAMA1 is dispensable for meiosis but important for ascosporogenesis in Fusarium graminearum. Issue 5 (18th March 2019) - Hao, Chaofeng; Yin, Jinrong; Sun, Manli; Wang, Qinhu; Liang, Jie; Bian, Zhuyun; Liu, Huiquan; Xu, Jin‐Rong
Summary: Ascospores are the primary inoculum in Fusarium graminearum . Interestingly, 70 of its genes have premature stop codons (PSC) and require A‐to‐I editing during sexual reproduction to encode full‐length proteins, including the ortholog of yeast Ama1, a meiosis‐specific activator of APC/C. In this study, we characterized the function of FgAMA1 and its PSC editing. FgAMA1 was specifically expressed during sexual reproduction. The Fgama1 mutant was normal in growth and perithecium formation but defective in ascospogenesis. Instead of forming four‐celled, uninucleate ascospores, Fgama1 mutant produced oval, single‐celled, binucleated ascospores by selfing. Some mutant ascospores began to bud and underwent additional mitosis inside asci. Expression of the wild‐type or edited FgAMA1 but not the uneditable allele complemented Fgama1 . In the Fgama1 x mat‐1‐1 outcross, over 60% of the asci had eight Fgama1 or intermediate (elongated but single‐celled) ascospores, suggesting efficient meiotic silencing of unpaired FgAMA1 . Deletion of FgPAL1, one of the genes upregulated in Fgama1 also resulted in defects in ascospore morphology and budding. Overall, our results showed that FgAMA1 is dispensable for meiosis but important for ascospore formation and discharge. In F. graminearum, whereas some of its targets are functional during meiosis, FgAma1 may target other proteins that function after spore delimitation. Abstract : Like its yeast ortholog Ama1, a meiosis‐specific activator of APC/C, FgAMA1 was specifically expressed during sexual reproduction and required RNA editing to encode the full‐length protein. The Fgama1 deletion mutant was defective only in ascospore morphology, budding and discharge. Meiotic silencing of FgAMA1 also resulted in the formation asci with eight mutant or intermediate ascospores, indicating that FgAMA1 is dispensable for meiosis but important for ascospore formation and discharge.